FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN DIARE PADA BALITA - Rahayu Setyaningsih; Diyono Diyono (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2020)
Background. Based on data from the Health Profile of Central Java Province on 2017, the proportion of diarrhea cases handled in Central Java in 2017 was 55.8%, the highest incidence of diarrhea was handled in Magelang, Surakarta and Sukoharjo. Factors that influence the occurrence of diarrhea include nutritional status, socioeconomic, health information, socio-culture, food sanitation, allergies and digestive tract infections. Research Objective. To find the factors that influence the incidence of diarrhea. Subjects and Methods. Subject Population of mothers and toddlers, in Posyandu Kadilangu Village with 57 samples. Method is non-experimental research with correlation approach. Data were collected using a questionnaire, analyzed using chi square. Results. All factors are influence diarhhea, nutritional status (p = 0.046), food sanitation (p = 0.001), socioeconomic (p = 0.001) and health information (p = 0.001). Conclusion. There is a relationship between nutritional status, food sanitation, socioeconomic and health information with the incidence of diarrhea. Keywords: diarrhea, health information, nutritional status, sanitation, social economic Korespondensi: Rahayu Setyaningsih. STIKES PANTI KOSALA SURAKARTA. Jalan Raya Solo - Baki KM. 4 Gedangan, Grogol, Sukoharjo, Jawa Tengah. Email: rahayusetyaningsih78@gmail.com